2020
DOI: 10.1177/2054358120975545
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Peritoneal Dialysis in Saskatchewan Canada: Results From a Province-Wide Survey

Abstract: Background: Peritoneal dialysis (PD) is an underutilized, therapeutic option to in-center hemodialysis (HD), given its similar survival and clinical efficacy but provides lifestyle benefits and cost savings. Despite these advantages, PD prevalence rates remains below 20% in many Canadian jurisdictions. Objectives: The primary objective of this study was to identify and assess patient-perceived barriers to PD implementation in Saskatchewan. The secondary objectives were to examine variations in patient-perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 45 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…PD provides several advantages over HD via assuring RKF, haemodynamic stability, flexibility and autonomy, less restricted diet and averting the need for vascular access. 3,22 Even though it has a plethora of advantages, most patients who need maintenance KRT avoid PD. Prasad et al found in a multicentre cross-sectional observational survey study that the main patient-reported barriers to PD were lack of awareness and knowledge about PD and fears surrounding safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PD provides several advantages over HD via assuring RKF, haemodynamic stability, flexibility and autonomy, less restricted diet and averting the need for vascular access. 3,22 Even though it has a plethora of advantages, most patients who need maintenance KRT avoid PD. Prasad et al found in a multicentre cross-sectional observational survey study that the main patient-reported barriers to PD were lack of awareness and knowledge about PD and fears surrounding safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies adjusted for comorbidities have found no mortality differences or better survival with PD than HD. 3 However, PD mortality decreased in the last decade due to biocompatible solutions and advances in PD technologies. 4,5 Furthermore, PD provides several advantages over HD, including preserving residual kidney function (RKF), haemodynamic stability, autonomy and flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for the disparity in utilization and the barriers to home dialysis in First Nations communities in Saskatchewan need to be addressed to improve quality of care. 15 …”
Section: Home-based Dialysis—peritoneal Dialysis (Pd) and Home Hemodialysis (Hhd)mentioning
confidence: 99%